Exploring the dynamics of user experience and interaction in XR-enhanced robotic surgery: a systematic review - Li, Yaning; Li, Meng; Zheng, Shucheng; Yang, Luxi; Peng, Lanqing; Fu, Chiyang; Chen, Yuexi; Wang, Chenxi; Chen, Chenyi; Li, Bingyan; Xiong, Boyuan; Breschi, Sofia; et al. (Frontiers in Virtual Reality, 2024)
Robotic surgery, also known as robotic-assisted surgery (RAS), has rapidly evolved during the last decade. RAS systems are developed to assist surgeons to perform complex minimally invasive surgeries, and necessitate augmented interfaces for precise execution of these image-guided procedures. Extended Reality (XR) technologies, augmenting the real-world perception via integrating digital contents, show promise in enhancing RAS efficacy in various studies. Despite multiple reviews on technological and medical aspects, the crucial elements of human-robot interaction (HRI) and user experience (UX) remain underexplored. This review fills this gap by elucidating HRI dynamics within XR-aided RAS systems, emphasizing their impact on UX and overall surgical outcomes. By synthesizing existing literature, this systematic review study identifies challenges and opportunities, paving the way for improved XR-enhanced robotic surgery, ultimately enhancing patient care and surgical performance.